Math, asked by deepakmaurya962488, 5 months ago

integral of
 \sqrt{tanx}

Answers

Answered by mathdude500
2

\large\underline{\bold{Given \:Question - }}

 \tt \: Evaluate \:  \int \: \sqrt{tanx} \: dx

\large\underline{{ \bf \: Solution :-  }}

\begin{gathered}\Large{\bold{{\underline{Formula\:Used - }}}}  \end{gathered}

 \boxed{ \tt \:  \int\dfrac{dx}{ {x}^{2} +  {a}^{2}  }  = \dfrac{1}{a}  {tan}^{ - 1} \bigg( \dfrac{x}{a}  + c\bigg) + c}

 \boxed{ \tt \:  \int\dfrac{dx}{ {x}^{2}  -   {a}^{2}  }  = \dfrac{1}{</strong><strong>2</strong><strong>a}  log\bigg(\dfrac{x - a}{x + a}\bigg) + c}

Consider

\rm :\longmapsto\: Let \:  I \:  = \int \: \sqrt{tanx}dx -  -  - (1)

\rm :\longmapsto\:\:  \:  \boxed{ \bf \:Put \: \sqrt{tanx} = y }

\rm :\implies\:tanx =  {y}^{2}

\rm :\implies\: {sec}^{2} x = 2y\dfrac{dy}{dx}

\rm :\implies\: {sec}^{2} x \: dx = 2ydy

\rm :\implies\:dx = \dfrac{2ydy}{ {sec}^{2}x }

\rm :\implies\:dx \:  =  \: \dfrac{2y \: dy}{1 +  {tan}^{2}x }

\rm :\implies\:dx \:  =  \: \dfrac{2y \: dy}{1 +  {y}^{4} }

So,

Equation (1) can be rewritten as

\rm :\longmapsto\: I = \int \: y \times \dfrac{2y}{ {y}^{4} + 1 } dy

\rm :\longmapsto\: I = \int \: \dfrac{ {2y}^{2} }{ {y}^{4} + 1 } dy

\rm :\longmapsto\: I = \int \: \dfrac{ {y}^{2}  +  {y}^{2} }{ {y}^{4}  + 1} dy

\rm :\longmapsto\: I = \int \: \dfrac{ {y}^{2}  +  {y}^{2}  + 1 - 1}{ {y}^{4}  + 1} dy

\rm :\longmapsto\: I = \int \: \dfrac{( {y}^{2}   + 1)+  ({y}^{2} - 1) }{ {y}^{4}  + 1} dy

\rm :\longmapsto\: I = \int\dfrac{ {y}^{2}  + 1}{ {y}^{4}  + 1} dy + \int\dfrac{ {y}^{2} - 1 }{ {y}^{4} + 1 } dy

 \boxed{ \tt \: Divide  \: numerator  \: and \:  denominator  \: by \:  {y}^{2} }

\rm :\longmapsto\: I = \int\dfrac{1 + \dfrac{1}{ {y}^{2} } }{ {y}^{2}  +  \dfrac{1}{ {y}^{2} } } dy + \int\dfrac{1  -  \dfrac{1}{ {y}^{2} } }{ {y}^{2}  +  \dfrac{1}{ {y}^{2} } } dy

\rm :\longmapsto\: I = \int\dfrac{1 + \dfrac{1}{ {y}^{2} } }{ {y}^{2}  +  \dfrac{1}{ {y}^{2}  }  - 2 + 2} dy + \int\dfrac{1  -  \dfrac{1}{ {y}^{2} } }{ {y}^{2}  +  \dfrac{1}{ {y}^{2} }  + 2 - 2} dy

\rm I = \int\dfrac{1 + \dfrac{1}{ {y}^{2} } }{  { \bigg (y  -  \dfrac{1}{y}  \bigg)}^{2}   + 2 } dy + \int\dfrac{1  -  \dfrac{1}{ {y}^{2} } }{  { \bigg (y   +   \dfrac{1}{y}  \bigg)}^{2}    -  2 } dy -  - (2)

Now,

\rm :\longmapsto\:Put \: y - \dfrac{1}{y}  = t

\rm :\implies\:(1 + \dfrac{1}{ {y}^{2} } )dy = dt

And

\rm :\longmapsto\:Put \: y  +  \dfrac{1}{y}  = z

\rm :\implies\:(1 - \dfrac{1}{ {y}^{2} } )dy = dz

So, equation (2) can be rewritten as

 \tt \:  I = \dfrac{dt}{ {t}^{2}  +  2 }  + \dfrac{dz}{ {z}^{2}   -  2}

 \tt \:  I = \dfrac{dt}{ {t}^{2}  +   {( \sqrt{2}) }^{2}  }  + \dfrac{dz}{ {z}^{2}   -   {( \sqrt{2}) }^{2} }

\bf\implies \: I = \dfrac{1}{ \sqrt{2} } {tan}^{ - 1}  \dfrac{t}{ \sqrt{2} }  + \dfrac{1}{2 \sqrt{2} } log \bigg(\dfrac{z -  \sqrt{2} }{z +  \sqrt{2} }  \bigg) + c

\bf\implies \: I = \dfrac{1}{ \sqrt{2} } {tan}^{ - 1}  \dfrac{y   -   \dfrac{1}{y}}{ \sqrt{2} }  + \dfrac{1}{2 \sqrt{2} } log \bigg(\dfrac{y    +    \dfrac{1}{y} -  \sqrt{2} }{y  +  \dfrac{1}{y} +  \sqrt{2} }  \bigg) + c

 \tt \:  I = \dfrac{1}{ \sqrt{2} }  {tan}^{ - 1}  \bigg( \dfrac{ {y}^{2} - 1 }{y \sqrt{2} } \bigg) + \dfrac{1}{2 \sqrt{2}}  log(\bigg( \dfrac{ {y}^{2}   +1   - y \sqrt{2} }{ {y}^{2}    + 1  +  y\sqrt{2} } \bigg))  + c

 \tt \:  I = \dfrac{1}{ \sqrt{2} } {tan}^{ - 1}\bigg(\dfrac{tanx - 1}{ \sqrt{2tanx} }  \bigg) + \dfrac{1}{2 \sqrt{2} } log\bigg( \dfrac{ tanx + 1 -  \sqrt{2tanx}  }{tanx + 1 +  \sqrt{2tanx} } \bigg)  + c

Similar questions